El modelo de control de gestión en las empresas de servicios públicos domiciliarios en Colombia: balance y desafíos durante la vigencia de la Ley 142 (2017)
The management control model of public services companies in Colombia is a model that has shortcomings, because its organizational structure composed of the regulatory commissions and the Public Services Superintendence in conjunction with the regulatory framework that governs it, has not managed to contribute to the State’s goal of guaranteeing well-being for the entire population, because there are still regions with deficiencies in coverage and quality in the provision of public services.The financial problems of important lending companies as a result of corruption and inefficient public management, show failures in the control systems that are affected by external factors such as regulation and the intervention of political actors in said regulation, the regional context, the sector where they operate and internal factors such as the absence of corporate governance, inopportune and unreliable information systems, poor planning and the lack of management control systems within the organization that not only promote financial control but also an evaluation more integral of public management.